Listeria monocytogenes and Listeriosis: The Global Enigma - Christy E. Manyi-Loh; Ryk Lues (Foods)
Listeria monocytogenes is an intracellular, Gram-positive, non-spore-forming, non-encapsulated, facultative anaerobic, rod-shaped, and psychrotrophic food-borne pathogen that causes the infection, listeriosis, thus it attracts great attention following listeriosis outbreaks, which are often associated with high mortality rates. The prevalence of listeriosis is quite low globally; however, the most recent and deadliest outbreak occurred in South Africa, during which 216 persons lost their lives. L. monocytogenes is endowed with the potential to multiply through a wide range of harsh environmental conditions, forming biofilms on varying surfaces in the food industry, as well as having persistent and antibiotic-resistant cells, which pose a major threat and burden to the ready-to-eat food industry. A more frustrating characteristic of this bacterium is its strain divergence, alongside an increased level of antibiotic resistance registered among the strains of L. monocytogenes recovered from food, humans, and environmental sources, especially to those antibiotics involved in the treatment of human listeriosis. Antibiotic resistance exerted by and among pathogenic food-borne microbes is an ongoing public health menace that continues to be an issue. Against this background, a thorough search into different databases using various search engines was performed, which led to the gathering of salient information that was organised, chronologically, based on Listeria monocytogenes and listeriosis. Altogether, the findings elaborated in this study present up-to date knowledge on different aspects of this pathogen which will improve our understanding of the mystery associated with it and the ways to prevent and control its dissemination through ready-to-eat foods. In addition, constant monitoring of the antibiotic resistance profiles of strains of L. monocytogenes from varying sources detected changes, giving an update on the trend in antibiotic resistance. Overall, monitoring of bacterial contamination serves as the key aspect in the control of the food safety output in the food industry.